1977
DOI: 10.1139/z77-001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pregnancy failure in the wild meadow vole, Microtus pennsylvanicus

Abstract: Normal and blocked pregnancy were studied in the meadow vole, Microtus pennsylvanicus (Ord), in the laboratory, on individuals bred from wild stock caught near Sudbury, Ontario. The results were then compared with those obtained from wild voles trapped from quadrats during the summers of 1969 and 1970.Criteria were found for distinguishing between individuals in which pregnancy had been blocked and those in which it had not, under laboratory conditions. Nursing females were not found to be susceptible to male-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In other species of rodents, contact with another breeding female may cause reproductive cessation as a result of pseudopregnancy (Brown 1985a), estrus suppression (Hoover and Drickamer 1979;McClintock 198 1 ) , and pregnancy block (Mallory and Brooks 1980). Reproductive cessation may be involved in microtine demography, because at high population densities many adult females stop breeding (Mallory and Clulow 1977). This may explain why breeding, nonpregnant females preferred the odor of males to the odor of other females, but pregnant females, who can have their pregnancies blocked by unfamiliar males, did not (Clulow and Langford 197 1).…”
Section: Discussionmentioning
confidence: 99%
“…In other species of rodents, contact with another breeding female may cause reproductive cessation as a result of pseudopregnancy (Brown 1985a), estrus suppression (Hoover and Drickamer 1979;McClintock 198 1 ) , and pregnancy block (Mallory and Brooks 1980). Reproductive cessation may be involved in microtine demography, because at high population densities many adult females stop breeding (Mallory and Clulow 1977). This may explain why breeding, nonpregnant females preferred the odor of males to the odor of other females, but pregnant females, who can have their pregnancies blocked by unfamiliar males, did not (Clulow and Langford 197 1).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the phenomenon also suggests that it may have a role in controlling population density (Chipman, Holt & Fox, 1966;Clulow & Clarke, 1968 ;Whitten & Bronson, 1970), and Mallory (1972) has suggested that pregnancy blocking may be involved in the population fluctuations of microtine rodents. A number of variables, however, may affect the importance of pregnancy blocking to animal populations in the wild : in mice, laboratory experiments indicate that some strains are more susceptible than others (Chapman & Whitten, 1969) and that blocking effectiveness may be reduced by grouping the females (Bruce, 1963), pre-exposing the females to many males, or the continued presence of the stud male (Parkes & Bruce, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…According to these hypotheses, frequent interactions between individuals at high population density result in reduced reproduction and increased mortality through social stress (Christian 1980), infanticide (Mallory and Brooks 1980), and strange male-induced pregnancy block (Mallory and Clulow 1977). Social interactions are thus assumed to be primarily stressful and agonistic .…”
Section: Introductionmentioning
confidence: 99%